The complexities of integrating evidence-based preventative health into England's NHS: lessons learnt from the case of PrEP - Tehseen Khan; Clare Coultas; Katharina Kieslich; Peter Littlejohns (BMC, 2023)
Abstract Background The integration of preventative health services into England's National Health Service is one of the cornerstones of current health policy. This integration is primarily envisaged through the removal of legislation that blocks collaborations between NHS organisations, local government, and community groups. Aims and objectives This paper aims to illustrate why these actions are insufficient through the case study of the PrEP judicial review. Methods Through an interview study with 15 HIV experts (commissioners, activists, clinicians, and national health body representatives), we explore the means by which the HIV prevention agenda was actively blocked, when NHS England denied responsibility for funding the clinically effective HIV pre-exposure prophylaxis (PrEP) drug in 2016, a case that led to judicial review. We draw on Wu et al.'s (Policy Soc 34:165-171, 2016) conceptual framing of 'policy capacity' in undertaking this analysis. Results The analyses highlight three main barriers to collaborating around evidence-based preventative health which indicate three main competence/capability issues in regard to policy capacity: latent stigma of 'lifestyle conditions' (individual-analytical capacity); the invisibility of prevention in the fragmented health and social care landscape related to issues of evidence generation and sharing, and public mobilisation (organizational-operational capacity); and institutional politics and distrust (systemic-political capacity). Discussion and conclusion We suggest that the findings hold implications for other 'lifestyle' conditions that are tackled through interventions funded by multiple healthcare bodies. We extend the discussion beyond the 'policy capacity and capabilities' approach to connect with a wider range of insights from the policy sciences, aimed at considering the range of actions needed for limiting the potential of commissioners to 'pass the buck' in regard to evidence-based preventative health.